Effect of Helper Lipids on Stability and Transfection Activity of Lyophilized Lipoplex Formulations of Antisense and DOTAP Nanoliposomes: Stability and transfection activity of lyophilized lipoplex formulations - Ali Mohammad Tamaddon; Mozhgan Nikravesh; Hossein Niknahad (Iranian Journal of Pharmaceutical Sciences, 2011)
Survivin, an inhibitor of apoptosis protein is highly expressed in most cancers and considered as an attractive target for cancer antisense therapy. To vectorize antisense molecules, cationic nanoliposomes are generally used; however, their complexes are too instable, during shelf-life and upon exposure to blood components and extracellular matrix, to be used in-vivo. The present study aimed to develop fresh and lyophilized formulations of antisense/DOTAP nanoliposomes with different helper lipids and compare their shelflife and biologic stabilities and their transfection activities in tumor cell lines. DOTAP nanoliposomes in combination with different helper lipids were prepared in HEPES buffer (20 mM, pH=7.4) by thin-layer hydration followed by thermobarrel extrusion and PTFE membrane filter sterilization. Nanoliposomes were characterized regarding their particle size distribution, final lipid recovery and physical stability. Following antisense loading by direct addition through electrostatic attraction, the degree of complexation was determined by ethidium bromide displacement assay. To stabilize the formulations, they were freezedried with 10% sucrose. The potential of the lyophilized and fresh formulations of FITC-labeled antisense to transfect different cell lines (SK-BR-3, MCF-7) was studied by flow cytometry. Fresh nanoliposomes of different formulations had a size in range of 50-100 nm. The degree of complex formation with antisense was determined almost 70-80% (N/P 2) which decreased as incubated with either PBS or complete medium and heparin sulfate. Their average sizes significantly changed after preservation for few days at 4 °C.Lyophilization process compromised the particle size distribution and antisense loading efficiency of different formulations except for DOTAP/DOPE (1:1 mole ratio) which did not change significantly. Both fresh and lyophilized formulations exhibited the highest transfection activity at comparable levels especially in SK-BR-3 cells. As a conclusion, lyophilization process could promote stability and preserve transfection activity of the antisense complexes of DOTAP/DOPE (1:1) nanoliposomes.